Apply PSO into cloud storage task scheduling with QoS preference awareness - Juan WANG; Fei LI; Lu-qiao ZHANG (Tongxin xuebao)
The task scheduling algorithm in cloud storage area with QoS preference awareness was studied.Firstly,the differences between cloud storage and cloud computing were pointed,and exist matrix was used to avoid the creation of useless solutions.Secondly,QoS factors were summarized into three classes:time,cost and quality classes.Based on the three classes,the fitness function of the PSO was improved by using weighted factors to adjust the QoS preference.The simulation results release that PSO is not fit for the overall scheduling when the task distributions of different degrees are unevenness because the QoS demand of wide distribution tasks may cover the QoS demand of other tasks.So a hierarchical scheduling based on degree is necessary.The simulation results show that the improved hierarchical PSO scheduling algorithm can aware the QoS preference relevantly.